A Simple Method for Predicting Friction Sensitivity of Quaternary Ammonium‐Based Energetic Ionic Liquids. Issue 6 (3rd May 2018) - Jafari, Mohammad; Keshavarz, Mohammad Hossein; Joudaki, Fatemeh; Mousaviazar, Ali
Abstract: Friction sensitivity is an important safety parameter for assessment when working with new energetic ionic liquids (EILs) during mixing, pouring, sieving, priming and consolidation operations in working places. This work introduces a reliable method to predict friction sensitivity of quaternary ammonium‐based EILs, which are based on elemental composition of cation and anion of a desired ionic liquid as well as the contribution of specific cations and anions. For 47 EILs, the values of coefficient of determination (R 2 ) and Root Mean Squared Error (RMSE) of the new model are 0.9057 and 33 N, respectively. High accuracy of the novel method confirms that prediction of friction sensitivity of quaternary ammonium‐based EILs is not necessarily enhanced by greater complexity. Abstract :